Effect of incinerator fly ash in cement mortar toward compressive strength and leaching characteristic - Noorhidayu, Che Hasmi (2012)
Today, incinerator used to bum municipal solid waste widely in developed countries including Malaysia. MWS fly ash produced from incinerator will donated a percentage of the material is disposed in landfill. Due to the increasing costs of landfill and the current interest in sustainable development, a lot of research has been done to recycle MWS fly ash utilization in Malaysia. This study was focus on the investigation of compressive strengt~ the presence of heavy metal leaching and microstructure of MWSI fly ash. The mortars cured for 7, 28, 60 and 90 days were tested for the compressive strength. The specimens (raw material, 10 and 30% FA) at 28 days were testing for presence of heavy metal leaching by using InductivityCoupled Plasma (ICP) spectroscopy. Also, the specimens for mortar (30% FA) at age 28 days were tested by X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) test. From the result obtained the higher strength for compressive strength of MSWI fly ash mortar is 28.66 N/mm2 for mortar which is I 0% of total percentage MSWI fly ash that has been used in the specimens, but it still lower than control mortar (41.50 N/mm2) . Leaching rates of heavy metals (Cr, Cu, Pb, Zn, Mn, Co, Ni, Sr, Cd, Sn, Ba) were recorded lower than the standard US Environmental Protection Agency (USEPA). XRD test has shown increment of calcium silicate hydrate (C-SH) pattern for 28 and 90 days, while decreasing of pattern of calcite. This proves the presence of pozzolanic elements in mortar. SEM test also was strengthening the evidence that the form of change reaction of MSWI fly ash between 28 and 90 days. As a conclusion, MSWI fly ash safe to use as a replacement for cement in mortar by using solidification and stabilization process